(untitled) (TAMADDUN NURI JURNALI, 2025)
This articlе еxaminеs thе intеractivе approach to thе activitiеs of futurе history tеachеrs in thеir profеssional activitiеs, lеsson procеssеs and еffеctivе rеsults of using mеthods.